2014
DOI: 10.5761/atcs.cr.13-00041
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Multilayered Sutureless Repair for a Left Ventricular Blowout Rupture Caused by Myocardial Infarction in the Second Diagonal Branch Territory

Abstract: A left ventricular (LV) free wall rupture represents an emergency, especially if it is a blowout rupture. [1][2][3] The sutureless patch has been recently used to repair an LV free wall rupture. 4,5) However, using sutureless patches to repair a blowout rupture is controversial due to the later development of re-rupture or formation of a pseudoaneurysm. 6,7) In this paper, we report a case of LV blowout rupture that was caused by myocardial infarction in the second diagonal branch territory. It was treated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Padró et al reported 13 successful cases treated by sutureless repair [9]. They applied a polytetrafluoroethylene patch over the infarcted area that was attached to the heart surface with surgical glue.…”
Section: Resultsmentioning
confidence: 99%
“…Padró et al reported 13 successful cases treated by sutureless repair [9]. They applied a polytetrafluoroethylene patch over the infarcted area that was attached to the heart surface with surgical glue.…”
Section: Resultsmentioning
confidence: 99%